Exploring the effects of structure and melting on sweetness in additively manufactured chocolate - Johannes Burkard; Lucas Kohler; Sophia Caciagli; Nicolas Herren; Mark Kozamernik; Saskia Mantovani; Erich J. Windhab; Christoph Denkel (Scientific Reports, 2024)
Abstract In view of the health concerns associated with high sugar intake, this study investigates methods to enhance sweetness perception in chocolate without increasing its sugar content. Using additive manufacturing, chocolate structures were created from masses with varying sugar and fat compositions, where hazelnut oil served as a partial cocoa butter replacement. The study found that while variations in sugar content minimally affected the physical properties of the chocolate masses, hazelnut oil significantly modified melting behavior and consumption time. Chocolate masses with higher hazelnut oil content but similar sugar content exhibited a 24% increase in sweetness perception, likely due to accelerated tastant (i.e., sucrose) release into saliva. Multiphase structures, designated as layered, cube-in-cube, and sandwich structures, exhibited less sensory differences compared to the homogeneous control. Nonetheless, structures with hazelnut oil-rich outer layers resulted in an 11% increase in sweetness perception, even without sugar gradients. This suggests that tastant release plays a more critical role than structural complexity in modifying sweetness perception. This research highlights the efficacy of simpler multiphase structures, such as sandwich designs, which offer sensory enhancements comparable to those of more complex designs but with reduced manufacturing effort, thus providing viable options for industrial-scale production.